(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The ecological restoration of Cerrado ecosystems involves challenges pertinent to the fertilization of the substrate for seedlings in nursery, which are often produced by a single type of substrate. However, habitat heterogeneity suggests that the species may have different nutritional requirements. The objective was to assess the effect of substrate fertilization and nutritional supplementation by leaf in developing seedlings of Kielmeyera coriacea Mart. & Zucc. Eugenia dysenterica (Mart.) and DC Handroanthus impetiginosus (Mart. ex DC.) Mattos. The experiment was implemented in a 3x3 factorial completely randomized design (three types of substrates x three levels of foliar fertilization), with ten replicates. The treatments were tested by analysis of variance. For K. coriacea and H. impetiginosus, it is recommended to use a substrate composed of Soil + Manure (2:1), for E. dysenterica, it is recommended to use the complete substrate. Foliar fertilization is not recommended for all species. Regarding the soil analysis, organic matter, phosphorus and calcium were determinants in the formation of fertility groups for each of the major components of the Principal Component Analysis.